2009
DOI: 10.1097/aog.0b013e3181ae9c64
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Contraceptive Method Use Among Women With Systemic Lupus Erythematosus

Abstract: Available evidence indicates that many women with SLE can be considered good candidates for most contraceptive methods, including hormonal contraceptives. The benefits of contraception for many women with SLE likely outweigh the risks of unintended pregnancy in this population. Women with positive antiphospholipid antibodies are not good candidates for combined hormonal contraception given their elevated baseline risk of thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
6

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 32 publications
0
26
0
6
Order By: Relevance
“…A common misconception among women with SLE is that they "cannot use birth control", since the "classical" oestrogen-containing pill is generally contraindicated. The message should be that women with SLE can be considered good candidates for many contraceptive methods, including hormonal contraceptives and the most suitable one should be chosen individually [112]. The three main types of contraceptives are: barrier methods, intrauterine device (IUD) and hormonal method.…”
Section: Contraception Fertility and Assisted Reproductionmentioning
confidence: 98%
“…A common misconception among women with SLE is that they "cannot use birth control", since the "classical" oestrogen-containing pill is generally contraindicated. The message should be that women with SLE can be considered good candidates for many contraceptive methods, including hormonal contraceptives and the most suitable one should be chosen individually [112]. The three main types of contraceptives are: barrier methods, intrauterine device (IUD) and hormonal method.…”
Section: Contraception Fertility and Assisted Reproductionmentioning
confidence: 98%
“…In addition, the loss of estrogen or its receptors early in the life of experimental mouse models of SLE has provided convincing evidence showing that estrogens have an important role in the development and progression of the disease (5, 35, 43). Surprisingly, the contribution of estrogens to SLE disease progression in humans remains unclear, and understanding their role in the cardiovascular risk is complicated by the large body of literature pointing to cardioprotective actions of estrogens in women (22, 47) as well as their relatively safe use in women with SLE (3,7,8,20,26,31,40). Using an established experimental model of SLE (female NZBWF1 mice), we (12) recently reported that loss of estradiol in adulthood exacerbates the hypertension and renal injury, which, when considering that loss of estrogens early in life delays disease onset, suggests that there are distinct temporal effects of estrogens on SLE disease progression and its consequences.…”
mentioning
confidence: 99%
“…4,76,77 Os efeitos negativos de uma gravidez não planejada em pacientes lúpicas podem ser devastadores e isso deve ser levado em consideração na indicação de contracepção. Entretanto, ACO devem ser evitados em mulheres com LES e história de doença vascular, nefrite ou anticorpos antifosfolí-pides (categoria 4).…”
Section: Lúpus Eritematoso Sistêmicounclassified
“…Entretanto, ACO devem ser evitados em mulheres com LES e história de doença vascular, nefrite ou anticorpos antifosfolí-pides (categoria 4). 46,77 …”
Section: Lúpus Eritematoso Sistêmicounclassified